2009
DOI: 10.1134/s1068162009030133
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of quercetin-3-O-glucoside, a known plant flavonoid

Abstract: Cytotoxic, phytotoxic, antimicrobial and antioxidant effects of quercetin 3-O-glucoside (Q3G) isolated by HPLC from aerial parts of Prangos ferulaceae was studied by MTT assay, lettuce germination assay, disk diffusion and DPPH method. Our results showed that Q3G exhibits high antioxidant effect with RC(50) of 22 microg/mL, it has low cytotoxicity and no antibacterial effects. Q3G exhibits high phytotoxic effect with IC(50) value of 282.7 microg/ml, as well. It is assumed that Q3G does not play a defense role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 7 publications
1
58
1
4
Order By: Relevance
“…in the plant have high antioxidant activity (Sajjadi and Mehregan, 2003;Coruh et al, 2007). Contrary to this, the flavonoid, quercetin-3-0-glucoside, in the extract from aerial parts of the plant did not exhibit antioxidant activity in the study conducted by Razavi et al 2009. According to the results of DPPH test in our study, all fruit extracts exhibited a slightly antioxidant activity.…”
contrasting
confidence: 37%
“…in the plant have high antioxidant activity (Sajjadi and Mehregan, 2003;Coruh et al, 2007). Contrary to this, the flavonoid, quercetin-3-0-glucoside, in the extract from aerial parts of the plant did not exhibit antioxidant activity in the study conducted by Razavi et al 2009. According to the results of DPPH test in our study, all fruit extracts exhibited a slightly antioxidant activity.…”
contrasting
confidence: 37%
“…1 R 1 =H; R 2 =H 2 R 1 =CH 3 ; R 2 =H 3 R 1 =H; R 2 =glicose A ocorrência destes flavonóides já foi relatada anteriormente para outras espécies vegetais. A quercetina 3-O-β-D-glicosídeo foi isolada de Prangos ferulaceae (Apiaceae) (Razavi et al, 2009), Euphorbia retusa (Euphorbiaceae) (Harraz, 2009), Rosa nutkana (Rosaceae) (Jovel et al, 2007) e de Desmostachia bipinnata (Gramineae) (Awaad et al, 2008). A quercetina 3-Osoforosídeo também está presente em Pterogyne nitens (Caesalpinioideae) (Regasini et al, 2008) e Bassia muricata (Chenopodiaceae) (Kamel et al, 2001), enquanto que das espécies Salicornia herbacea (Chenopodiaceae) (Lee et al, 2005) e Astragalus corniculatus (Fabaceae) (Krasteva et al, 2008) já foi isolada a isoraminetina 3-glicosídeo.…”
Section: Resultsunclassified
“…The compound demonstrated antiproliferative activity in leukemia HL60 cells [78] . Flavonoids (quercetin, quercitrin, IQ, and rutin) isolated from the leaves of Scutia buxifolia were evalu ated against chromosomal damage induced by H2O2 in human lymphocytes and the result demonstrated that quercetin, IQ, and rutin recovered the mitotic index and chromosomal instability more than quercitrin did after treatment with H2O2 [30] . Studies intended to evaluate the plantassociated quercetin glycosides and human phase Ⅱ quercetin meta bolites, actually found by analyzing human biological fluids that following the consumption of quercetin con taining foods, these compounds can interact with the estrogen receptors (ER).…”
Section: Lymphoproliferative Cancermentioning
confidence: 99%
“…They concluded that flavonoids decreased the chromosomal damage by reducing the oxidative stress. Furthermore, Razavi et al [30] showed that Q3G has cytotoxic and antibacterial effects that are lower than its antioxidant potential, which justifies its application as a pharmacological agent to protect against ROS responsible for exacerbating tissue damage.…”
Section: Effects Of Iq In Cancermentioning
confidence: 99%